Satans art of deception - Sheikh Yusuf Estes; Millikan, David; One Islam Production; ICRA Youth Centre, Inc.; Saba Islamic Media ([Australia] : One Islam Production ; Kuala Lumpur : Saba Islamic Media (distributor), 2004)
This an open dialogue between Sheikh Yusuf Estes, the former priest and Christian preacher and Rev. Dr. David Millikan, the uniting church minister, BA, BD, PHD on satans: the art of deception, diverting the servants of God to the pathway of hell
Title from title screen
Speakers: Sheikh Yusuf Estes, David Millikan
Keywords: Islam -- Relations -- Christianity; Islam; Christianity and other religions -- Islam